Effect of solar heater boxes on seed quality of adzuki bean (Vigna angularis) - M. E. Elhadaa, Ragaa; Muhamad Awang, Rita; Omar, Dzolkhifli; Sinniah, Uma Rani; Grozescu, Ionel Vaieriu (International Organization of Scientific Research, 2017)
The effect of solar heater boxes on germination, moisture content and seedling characteristics of adzuki bean beans seeds V. angularis was determined using cardboard and plywood solar heater boxes. Results showed that, exposure to cardboard and plywood solar heater boxes did not show enormous effect on germination characters for adzuki bean seeds. In addition, experiment in oven was done for more verification. Exposure to temperatures of 40, 50, 60, and 70°C did not affect germination of adzuki bean seeds.